Changes in bone mineral density and bone turnover in patients on 'drug holiday' following bisphosphonate therapy: real‐life clinic setting. (8th February 2016) - Roberts, J.; Castro, C.; Moore, A.E.B.; Fogelman, I.; Hampson, G.
Summary: Objectives: Treatment discontinuation after long‐term bisphosphonate (BP), termed a 'drug holiday', has been proposed to reduce the risk of BP‐associated complications. The duration of treatment cessation remains unclear. Changes in bone mineral density (BMD), bone turnover markers (BTMs) and their relationship with FRAX were assessed to help determine the optimum length of a 'drug holiday'. Methods: A retrospective analysis of 134 patients (13M, 121F) aged [mean (SD)] 68·4 (8·2) years who discontinued BPs after treatment for 5·9 (3·0) years for osteoporosis was undertaken. BMD at the lumbar spine (LS), total hip (TH), and femoral neck (FN) and biochemical parameters including serum 25 (OH) vitamin D, bone turnover markers (plasma CTX, P1NP) and FRAX scores were determined at discontinuation, 12–18 months and 24–30 months off treatment. Results: BMD decreased significantly at the LS [% change mean (SD): −0·94 (3·6), P = 0·008], TH [−1·4 (2·4), P < 0·001] and FN [−1·8 (4·4), P < 0·001] after treatment discontinuation for 12–18 months. In the subgroup who remained off treatment for 24–30 months, a progressive decline in BMD was seen at the TH and FN with total % decrease of −2·52 (3·5) and −2·7 (4·76), P < 0·001, respectively. CTX and P1NP increased significantly at 12–18 months after discontinuation [% change CTX: 95 (88), P < 0·001, P1NP: 88 (73), P < 0·001]. FRAX scores were significant predictors of % change in BMD at the FN ( P < 0·05), independently of bone turnover and vitamin D status. In summary, our data show that following a 'drug holiday', the use of DEXA scans, BTMs and FRAX may help guide when to resume treatment.